2006
DOI: 10.1093/hmg/ddl430
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected mosaicism of R201H-GNAS1 mutant-bearing cells in the testes underlie macro-orchidism without sexual precocity in McCune–Albright syndrome

Abstract: McCune-Albright syndrome (MAS), usually presenting with polyostotic bone dysplasia, café-au-lait skin lesions and sexual precocity, results from a somatic activating mutation of the GNAS1 gene, which encodes the Gs-alpha protein involved in signalling of several G-protein-coupled receptors. The clinical spectrum depends on tissue distribution of mutant-bearing cells. Sexual precocity has been ascribed to the occurrence of a mutant GNAS1 allele in the gonadal anlage, from which all somatic cells of the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
0
34
1
3
Order By: Relevance
“…However, macroorchidism was not associated with manifestations of hyperandrogenism, probably due to an autonomous hyperfunction of Sertoli cells, with no activation of Leydig cells. In fact, it has been recently demonstrated that GNAS1 allele mutation may be present only in Sertoli cells (18), resulting in isolated Sertoli cell hyperfunction (15). In the present case, on the contrary, clinical, biochemical, and histological findings altogether suggest an isolated Leydig cell hyperfunction, with no premature activation of Sertoli cells.…”
Section: Discussioncontrasting
confidence: 63%
“…However, macroorchidism was not associated with manifestations of hyperandrogenism, probably due to an autonomous hyperfunction of Sertoli cells, with no activation of Leydig cells. In fact, it has been recently demonstrated that GNAS1 allele mutation may be present only in Sertoli cells (18), resulting in isolated Sertoli cell hyperfunction (15). In the present case, on the contrary, clinical, biochemical, and histological findings altogether suggest an isolated Leydig cell hyperfunction, with no premature activation of Sertoli cells.…”
Section: Discussioncontrasting
confidence: 63%
“…Therefore, serum AMH is a widely accepted biomarker of testicular activity during childhood (30,31,32,33,34,35,36). Furthermore, serum AMH has been postulated as a surrogate marker for the mass of functional Sertoli cells in patients with gonadal dysgenesis (37), hypogonadotropic hypogonadism (14,38) and Sertoli cell hyperplasia (39,40). In the present work, the significant correlation between testicular volume and AMH suggested that AMH levels reflect the degree of compensatory hypertrophy in prepubertal patients with monorchidism.…”
Section: European Journal Of Endocrinologymentioning
confidence: 52%
“…His elevated levels of IB and AMH are considered to be a marker of Sertoli cell activation which could account for the macroorchidism [25]. …”
Section: Discussionmentioning
confidence: 99%
“…While we did not analyze this patient’s testicular tissue, we previously studied and reported the case of a boy with MAS and macroorchidism with hyperfunction of Sertoli cells [25] similarly suggested by high levels of IB and AMH. In the first reported case, testicular biopsy and molecular study revealed isolated Sertoli cell hyperplasia, mosaic activation of the G s α gene in Sertoli cells and no Leydig cell maturation.…”
Section: Discussionmentioning
confidence: 99%